Analysis Of Factors Influencing Profitability (ROA) In The Digital Era: A Review Of E-Commerce Companies - Lastari, Devi Suci; Yuniar, Awaliyah Fadya; Sitinjak, Moses Aprildo Jerico; Sutardi, ⁠Fitrah Diraya; Riyandi, Riyandi; Sidik, Nur Halimah (Peneliti.net, 2025)
This research is a part of e-commerce profitability factor investigation, addressing Return on Assets (ROA) within the digital era. With the increasing demand for technology and internet usage, online businesses are facing problems that may have a drastic impact on their financial management skills along with providing them new opportunities. The scope of this research was the use of quantitative methods and the financial statement analysis of the giant enterprises in the e-commerce industry. The results of the study imply that technologies, digital marketing strategies, and cost-management are the major contributors to the entities' return on assets (ROA). This study is exploratory and seeks to provide practical recommendations to managers and employees of e-commerce companies, who will be affected by the digital transformation of the firm if they do not develop strategies to improve profitability.